"Idiopathic" Thrombosis in the Vertebrobasilar Arterial System in Young Men. Issue 5791 (1st January 1972) - Graham, D. I.; Adams, Hume
Abstract : Two young men died as a result of cerebellar infarction due to thrombosis in the vertebrobasilar arterial system in the absence of atheromatous stenosis, other identifiable intrinsic arterial disease, or embolism. In each case the swollen cerebellar infarct had produced tonsillar herniation and hydrocephalus.